School Milieu and Education Revenue: The Educational Environment and Student Achievement - F. Yazdanfar (University of Sofia, 2014)
This paper appraises an appropriate educational environment at a perfect school. A standard environment equipped with suitable facilities has fundamental effects on better and deeper learning materials and mental conditions of the students and their parents and, eventually, on their mental calmness and social progress. In the present survey, the geographical locations of the schools, good grades and the necessary equipment were discussed as the classroom is a place that has a direct impact on the education process. Then the rest of the school components with indirect but essential influences upon training were considered. In this review, it was also tried to consider the roles of administrative and logistic departments in students' achievement.